Hybrid Composites from Wheat Straw, Inorganic Filler, and Recycled Polypropylene: Morphology and Mechanical and Thermal Expansion Performance - Min Yu; Runzhou Huang; Chunxia He; Qinglin Wu; Xueni Zhao (International Journal of Polymer Science)
Reinforcing effect of hybrid filler including wheat straw (WS) and inorganic filler (heavy calcium carbonate, silicon dioxide, and fly ash) in recycled polypropylene (R-PP) has been investigated. The effects of individual filler (WS) and combined fillers (WS and inorganic filler) on morphological, mechanical, and thermal expansion and water absorption properties of hybrid composites were investigated. The flexural modulus and flexural strength were both reduced when reinforced with three kinds of inorganic fillers, respectively, which was possibly due to the poor interphase adhesion as observed in SEM. The high surface energy of heavy calcium carbonate due to its high acidic character provides an opportunity of better PP-heavy calcium carbonate interfacial interactions compared to PP-straw, PP-fly ash, and PP-SiO2 interface. The water absorption at saturation increased markedly by introduction of WS in it. The hybrid composites from WS and inorganic fillers showed better water absorption compared to those WS/PP composites. The thermal expansion of composites decreased with the increase of WS loading. Heavy calcium and SiO2 can obviously reduce the LCTE value of composite. At the 25% inorganic filler content, composites had the smallest LCTE values.